The Urgency of Reharmonization in Construction of The Stage Formation of Law - M Jeffri Arlinandes Chandra; Febrian Febrian; Bayu Dwi Anggono (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Indonesia is a state of law that relies on a rule of law formed as a basic rule in the state and society. The law as the primary basis must be made following the principles of the Formation of good law so that it is expected that later it can be applied and has binding legal force for all levels of society. However, the current situation is far from the expectation of the formation of good law. For example, the Formation of a job creation law which is considered not to involve the community actively, many articles are contrary to legal principles, disharmonized and unsynchronized between law. The formation of law seems in a hurry so there are many errors in writing (typo) and many other things. Therefore, it is necessary to reconstruct the stages in making good law. This paper uses normative research with a statutory approach, a comparative approach, and finally concludes with a conceptual approach where concepts that are considered suitable can be applied in Indonesia. This article provides two conclusions. First, the practice of harmonization, synchronization and consolidation of conceptions that have been well implemented but only exist at the planning and drafting stages of the Bill. While after the discussion/mutual agreement (plenary), no further harmonization and synchronization are carried out. Second, the post-discussion (plenary) re-harmonization stage can provide space for the implementation of educational facilities, consultations and publications of pre-validation and enactment of law that will be ratified in the form of meaningful public participation